Building resilience against biological hazards and pandemics: COVID-19 and its implications for the Sendai Framework - Djalante, Riyanti; Shaw, Rajib; DeWit, Andrew (Progress in disaster science, 2020)
2020 has become the year of coping with COVID-19. This year was to be the “super year” for sustainability, a year of strengthening global actions to accelerate the transformations required for achieving the 2030 agenda. We argue that 2020 can and must be a year of both. Thus we call for more utilisation of the health-emergency disaster risk management (Health-EDRM) framework to complement current responses to COVID-19 and the patent risk of similar phenomena in the future. To make our case, we examine current responses to COVID-19 and their implications for the SFDRR. We argue that current mechanisms and strategies for disaster resilience, as outlined in the SFDRR, can enhance responses to epidemics or global pandemics such as COVID-19. In this regard, we make several general and DRR-specific recommendations. These recommendations concern knowledge and science provision in understanding disaster and health-related emergency risks, the extension of disaster risk governance to manage both disaster risks and potential health-emergencies, particularly for humanitarian coordination aspects; and the strengthening of community-level preparedness and response.